ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SELAI SRIKAYA SUKA HATI DI PONTIANAK - Sri Wahyuningsih; Eva Dolorosa; Imelda Imelda (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to analyze what factors influence the purchasing decisions of consumers of srikaya Suka Hati in Pontianak. The population in this study are all consumers who buy the product. Sampling is taken using the method Convenience /Accidental Sampling, with a total sample of 100 respondents. This study used survey method with factor analysis. The results of this study indicate that there are nine new factors that influence consumer purchasing decisions on the products of srikaya Suka Hati namely product, distribution, motivation, social, perception, promotion, price, personal, and lifestyle. Keywords: Factor analysis, purchasing decision, srikaya Suka Hati.